1985
DOI: 10.1136/gut.26.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhoea and malabsorption in acquired immune deficiency syndrome: a study of four cases with special emphasis on opportunistic protozoan infestations.

Abstract: SUMMARY Chronic diarrhoea is frequent in acquired immune deficiency syndrome (AIDS) but has been poorly investigated so far. We report four patients with AIDS in whom diarrhoea and malabsorption were outstanding features, and who underwent extensive digestive investigations. Diarrhoea was a presenting symptom in all subjects and was of secretory type in three of them. D-xylose and vitamin B12 were malabsorbed in all cases; steatorrhea was found in the two patients who could ingest significant amounts of fat. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
1
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(63 citation statements)
references
References 28 publications
1
60
1
1
Order By: Relevance
“…The microsporidian protozoan organism Enterocytozoon bieneusi, first reported in 1985 [1,2], has been recognized as a human immunodeficiency virus (HIV)-associated intestinal opportunistic pathogen [1][2][3][4][5][6][7][8][9]. Preliminary epidemiological studies have indicated that it may be present in 10%-30% of severely immunodeficient HIV-infected adults with chronic diarrhea [3][4][5][6]9].…”
mentioning
confidence: 99%
“…The microsporidian protozoan organism Enterocytozoon bieneusi, first reported in 1985 [1,2], has been recognized as a human immunodeficiency virus (HIV)-associated intestinal opportunistic pathogen [1][2][3][4][5][6][7][8][9]. Preliminary epidemiological studies have indicated that it may be present in 10%-30% of severely immunodeficient HIV-infected adults with chronic diarrhea [3][4][5][6]9].…”
mentioning
confidence: 99%
“…Whilst infection may be asymptomatic, symptoms in immunocompromised patients, and especially in AIDS patients, may be severe and prolonged (Whiteside et al, 1984). In such patients a clinical picture similar to that found in cryptosporidiosis may occur and it is of interest that concomitant infection with both coccidians is not uncommon (Modigliani et al, 1985;Gelb and Miller, 1986). I. belli has been found in 15% of Haitian AIDS sufferers (de Hovits et al, 1986).…”
Section: Isospora Bellimentioning
confidence: 99%
“…These authors suggest that the homosexual or bisexual activity of oro-anal intercourse accounts for the relatively high prevalence (4.2%) of cryptosporidiosis in such patients compared with heterosexual male and female AIDS patients (2.1%). In immunocompromised patients, and particularly in AIDS patients, symptoms are prolonged with profuse watery diarrhoea which can be life-threatening (Malebranche et al, 1983;Modigliani et al, 1985;Gelb and Miller, 1986). Cryptosporidium spp.…”
Section: Cryptosporidium Sppmentioning
confidence: 99%
“…The clinical entity of Enterocytozoon bieneusi-related diarrhea first characterized by Modigliani and others 1 and Desportes and others 2 was originally considered to be a relentless, progressive, wasting condition with significant morbidity and mortality seen in severely immunosuppressed patients with CD4 cell counts generally less than 100 cells/ mm 3 . [1][2][3] Parasite eradication using metronidazole, albendazole, and thalidomide was considered problematic.…”
mentioning
confidence: 99%
“…[1][2][3] Parasite eradication using metronidazole, albendazole, and thalidomide was considered problematic. [4][5][6] Recent observations suggest that the clinical course of E. bieneusi-associated gastrointestinal infection has changed from its original description.…”
mentioning
confidence: 99%